All Days 2014
DOI: 10.2118/169159-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Experiments and Models for Conformance Control Microgels

Abstract: Water management in mature waterflooded reservoirs is a top priority to push more oil out and control water production. Excess water production through fractures and high permeability thief zones is a growing concern for sweep efficiency and oil production. Gel treatment has been applied widely to plug thief zones and reduce excess water production to improve macroscopic sweep efficiency. Field studies demonstrated that gel treatments can be applied successfully in mature and fractured reservoirs to reduce unw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…method is also using less amount of material that is economically effective especially within the time of low oil prices. 2,19 Some methods used to block high permeability zones which vary from chemical to mechanical treatments, or combinations of both, have been implemented in the industry. Initial trial to reduce water production involved mechanical isolation, cement squeezing, solid-slurry injection, and oil-water emulsion.…”
Section: Thismentioning
confidence: 99%
“…method is also using less amount of material that is economically effective especially within the time of low oil prices. 2,19 Some methods used to block high permeability zones which vary from chemical to mechanical treatments, or combinations of both, have been implemented in the industry. Initial trial to reduce water production involved mechanical isolation, cement squeezing, solid-slurry injection, and oil-water emulsion.…”
Section: Thismentioning
confidence: 99%
“…There are few studies about oil recovery from cores by polymeric particles (Wang 2010;Goudarzi et al 2014). Goudarzi et al (2014) conducted core flood experiments using micro gels (preformed particle gel, PPG) with a particles size of 100-200 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Goudarzi et al (2014) conducted core flood experiments using micro gels (preformed particle gel, PPG) with a particles size of 100-200 nm. It was shown that the micro gels can reduce the oil saturation of a Berea sandstone core in the tertiary mode.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations